Simulation analysis of DVR performance for voltage SAG mitigation: article / Mohd Saad Abd Rahim - Abd Rahim, Mohd Saad (2010)
Voltage sag is literally one of power quality problem and it become severe to industrial customers. Voltage sag can cause miss operation to several sensitive electronic equipments. That problem can be mitigating with voltage injection method using custom power device, Dynamic Voltage Restorer (DVR). This paper presents modeling and analysis of a DVR with pulse width modulation (PWM) based controller by using the Matlab/Simulink. The performance of the DVR depends on the efficiency of the control technique involved in switching the inverter. This paper proposed two control techniques which is PI controller (PI) and Fuzzy Logic controller (FL). Comprehensive results are presented to assess the performance of each controller as the best power quality solution. Other factors that also can affect the performance and capability of DVR are presented as well.